System and apparatus for the treatment of organic effluents - Idris, Azni (2006)
An apparatus for the treatment of organic effluents with substantially large COD and BOD₅ values is disclosed. Effluent is introduced into the tank for retention for a period of time before being discharge. The tank comprises of a first chamber to receive and pre-treat the effluent utilizing a sludge blanket, a second chamber containing media for the attachment of anaerobic bacteria and discharge. The tank comprises of a first chamber to receive and pre-treat the effluent utilizing a sludge blanket, a second chamber containing media for the attachment of anaerobic bacteria and discharge outlets to facilitate flow of biogas, treated effluents and waste sludge.